2020
DOI: 10.3390/genes11091088
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Antibiotic Resistance Genes in the Saliva of Healthy Omnivores, Ovo-Lacto-Vegetarians, and Vegans

Abstract: Food consumption allows the entrance of bacteria and their antibiotic resistance (AR) genes into the human oral cavity. To date, very few studies have examined the influence of diet on the composition of the salivary microbiota, and even fewer investigations have specifically aimed to assess the impact of different long-term diets on the salivary resistome. In this study, the saliva of 144 healthy omnivores, ovo-lacto-vegetarians, and vegans were screened by nested PCR for the occurrence of 12 genes conferring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Twelve studies were able to be compared to look at the presence of antibiotic resistance genes between different countries (Table 2) (Card et al., 2014; Collins et al., 2016; Diaz‐Mejia et al., 2002; Ioannidis et al., 2009; Jungermann et al., 2011; Manch‐Citron et al., 2000; Milanovic et al., 2020; Patterson et al., 2007; Rocas & Siqueira, 2012, 2013; Sun et al., 2012; Tang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were able to be compared to look at the presence of antibiotic resistance genes between different countries (Table 2) (Card et al., 2014; Collins et al., 2016; Diaz‐Mejia et al., 2002; Ioannidis et al., 2009; Jungermann et al., 2011; Manch‐Citron et al., 2000; Milanovic et al., 2020; Patterson et al., 2007; Rocas & Siqueira, 2012, 2013; Sun et al., 2012; Tang et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…From studies looking at antibiotic resistance genes in saliva samples in Europe, the most prevalent gene was erm (B) which was present in up to 97% of individuals (Milanovic et al., 2020). tet (B), tet (O) and tet (W) were all found to be the most common tetracycline resistance genes with tet (W) present in 100% of saliva samples in Italy (Milanovic et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples that were negative for each of the AR genes under study were further subjected to nested PCR assays designed to enhance the gene detection sensitivity, as previously reported by Garofalo et al [31]. The high sensitivity of the latter method was confirmed in recent studies aimed at detecting the same AR genes in different edible insects [14,16,17,19,20] as well as in human stool and saliva samples [30,33].…”
Section: Discussionmentioning
confidence: 78%
“…showed the abundance of ARGs against tetracycline (tetW and tetM) and erythromycin (ermB) in the Italian population. According to the Global Action Plan on Antimicrobial Resistance, screening of ARGs is one of the key objectives for minimizing the incidence of antibiotic resistance (Milanovi c et al 2020). Previous studies have demonstrated the presence of antibiotic resistance genes against macrolides, tetracyclines, b-lactams, fluoroquinolones, vancomycin and sulphonamide using metagenomics, and microarray analysis (Seville et al 2009;Sommer et al 2009;Hu et al 2014;van Schaik.…”
Section: Resultsmentioning
confidence: 99%